2018
DOI: 10.1111/fare.12311
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Relationship Functioning in Same‐Sex Couples: The Vulnerabilities of Internalized Homophobia and Outness

Abstract: Objective We examined whether high levels of internalized homophobia and low levels of openness about one's sexual identity (“outness”) were enduring vulnerabilities for same‐sex couples' relationship functioning. Background The vulnerability–stress–adaptation (VSA) model describes how stress can impact relationship functioning. This model has predominately been applied to the study of heterosexual couples, which leaves a dearth of literature on enduring vulnerabilities specific to same‐sex couples' relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 44 publications
(129 reference statements)
4
50
1
Order By: Relevance
“…Finally, more studies on clinical interventions focusing on the improvement of dyadic coping skills, such as the Couples Coping Enhancement Training (CCET) by Bodenmann and Shantinath (2004) or TOGETER by Falconier (2015) are needed. However, current research by Randall and Totenhagen shows promise in this area based on their research with sexual minority individuals experiencing stress due to their marginalized status (Randall et al, 2017a,b; Totenhagen et al, 2018).…”
Section: Future Directionsmentioning
confidence: 99%
“…Finally, more studies on clinical interventions focusing on the improvement of dyadic coping skills, such as the Couples Coping Enhancement Training (CCET) by Bodenmann and Shantinath (2004) or TOGETER by Falconier (2015) are needed. However, current research by Randall and Totenhagen shows promise in this area based on their research with sexual minority individuals experiencing stress due to their marginalized status (Randall et al, 2017a,b; Totenhagen et al, 2018).…”
Section: Future Directionsmentioning
confidence: 99%
“…First, in jurisdictions without legally recognized relationships, dyadic designs (e.g., actor-partner interdependence models, Smith et al, 2020 ) can be used to contrast outcomes in legal and non-legal parents while taking further partner characteristics (e.g., minority stress) into account. Daily fluctuations in legal vulnerability and stress spillover effects could be assessed by dyadic diary studies (Totenhagen et al, 2018 ; Cooper et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The development of models related to sexual minority health on the individual, couple, and family-level has proliferated in recent years. Future research could integrate legal vulnerability in the family resilience model (Prendergast and MacPhee, 2018 ), the relationship uncertainty model (Monk and Ogolsky, 2019 ), or adaptations of the vulnerability-stress-adaptation model (Karney and Bradbury, 1995 ; Totenhagen et al, 2018 ), among others. Conversely, researchers could link other concepts of legal meaning making for sexual minorities, such as legal consciousness (Hull, 2016 ), with legal vulnerability.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Totenhagen, Randall, and Lloyd () found that high levels of internalized homophobia and low levels of “outness” were shown to be potentially enduring vulnerabilities that affect both LGB individuals and their families. The burden of internalized sexual stigma can contribute to reduced authenticity and congruence, leading to identity concealment, which in turn can affect the quality of family relationships.…”
Section: Internalization Of Sexual Stigmamentioning
confidence: 99%